PERBANDINGAN LUTHER DAN CALVIN DALAM PENAFSIRAN TERHADAP KHOTBAH DI BUKIT - Joshua Timothy Siwalette (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2018)
The Sermon on the Mount is one of the most famous passages in the Bible, but unfortunately it has a polemic interpretation in the reformed circles. This article analyzes two interpretations of the Sermon on the Mount from two well-known reformed figures, John Calvin and Martin Luther, to discover the heart of the problem. This article shows that Calvin's interpretation is more responsible than Luther's, but there is a beautiful legitimate application that readers can learn from Luther. Keywords: Interpretation, Sermon on the Mount, John Calvin, Martin Luther, historical criticism, law and gospel.